PELAKSANAAN SITA EKSEKUSI TERHADAP OBYEK SITA EKSEKUSI (LAHAN) YANG BERADA DI WILAYAH PENGADILAN NEGERI SAMARINDA - Muhamad Revy Shadieva (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACT   A dispute occurs when a person controls or diminishes the rights of another person relating to maintaining the rights in question. In that case sometimes the parties in resolving it by means of the family (peace) but not infrequently from the concerned party to include the case to the District Court to be resolved.Execution is an act that is carried out by force against the losing party in the case. Usually, the action of confiscation of execution is only carried out after the defendant is declared defeated in the court process, and then the defendant's position turns into the executed party.That the execution in the Civil Procedure Law is the implementation of the verdict on the order and or led by the chairman of the District Court before the execution is given a warning (amazing). If heedless, then the execution is carried out.Execution as a legal action carried out by the court to the losing party in a case is a follow-up rule and procedure of the case examiner process. Therefore execution is nothing but an ongoing act of the entire civil legal process.Not all decisions of the Court that already have the force of law still require the forced execution by state tools, but only the decision of the Court of Condemnatoir which is a ruling that is punishing the defeated party to fulfill the achievement, and the defeated party does not want to carry it out voluntarily. Therefore, the execution will be done by force.Keywords: Sita Execution, land, verdict